Mystical Midrash - Schleicher, Marianne (Nordisk judaistik/Scandinavian Jewish Studies, 2003)
This article conceives of mystical midrash as the act of interpreting the details of a Torah verse with the purpose of entering a meditative or ecstatic state of union with God, in which the mystic by drawing down God’s insights can explain how the Torah verse mediates the micro-macrocosmic relation between God’s will and the course of history. However, since mystical midrash is such a rare phenomenon in Judaism, I have chosen to highlight the various approaches to the Torah in Jewish mysticism as a background for understanding why only one of these approaches qualifies for the epithet ‘mystical midrash’.